2011
DOI: 10.2174/138920111794295792
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic Steroid - and Exercise - Induced Cardio-Depressant Cytokines and Myocardial β1 Receptor Expression in CD1 Mice

Abstract: Few animal model studies have been conducted in order to evaluate the impact of androgenic anabolic steroids (AAS) supraphysiological doses on the cardiovascular system and myocardial injury. Twenty-five male CD1 mice (8-10 weeks old; 35g initial body weight) were randomized into three AAS treated groups and two control groups. The AAS mice received intramuscular Nandrolone Decanoate (DECA-DURABOLIN), vehicled in arachidis oil, for 42 days, twice per week, with different dosages, studying plasma lipid analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…Although the association between AAS and exercise may change exercise-induced physiological cardiac hypertrophy into pathophysiological hypertrophy, the physiological mechanisms of this change are still poorly understood (Riezzo et al, 2011a). Riezzo et al (2011a) reported increased heart weight, and cardiac hypertrophy in trained mice treated with high doses of nandrolone, and attributed this effect to an enhanced protein synthesis in response to the nandrolone administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the association between AAS and exercise may change exercise-induced physiological cardiac hypertrophy into pathophysiological hypertrophy, the physiological mechanisms of this change are still poorly understood (Riezzo et al, 2011a). Riezzo et al (2011a) reported increased heart weight, and cardiac hypertrophy in trained mice treated with high doses of nandrolone, and attributed this effect to an enhanced protein synthesis in response to the nandrolone administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between AAS and exercise may change exercise-induced physiological cardiac hypertrophy into pathophysiological hypertrophy, the physiological mechanisms of this change are still poorly understood (Riezzo et al, 2011a). Riezzo et al (2011a) reported increased heart weight, and cardiac hypertrophy in trained mice treated with high doses of nandrolone, and attributed this effect to an enhanced protein synthesis in response to the nandrolone administration. It has been also suggested that β-adrenoceptor-mediated mechanisms are involved in the development of cardiac hypertrophy (Hannan et al, 2003;Sethi et al, 2007;Riezzo et al, 2011b), depending on the type and stage of hypertrophy (Sethi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenously administered AAS induce cardiac hypertrophy in vitro and in vivo [4], [5]. Furthermore, high doses of AAS administered in conjunction with vigorous exercise training in mice leads to cardiac hypertrophy, increased inflammatory cytokine levels and significant stimulation of the sympathetic nervous system [6]. Therefore, the combination of such factors may predispose subjects to myocardial injury.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic AAS abuse results in different patterns of pathologic alterations which depend on dose, frequency and mode of use. The latency of sub-acute or chronic effect (multiple-dose treatments) can be the result of either drug accumulation or the sum of sub-toxic effects which, over time, may become evident in clear clinical symptoms unrelated to the kinetics of the substance in question [40]. Increases in total cholesterol occur with anabolic steroids and this has been shown to augment coronary artery response to catecholamines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been reported that the combined effects of vigorous training, anabolic steroid abuse and stimulation of the sympathetic nervous system, may dispose to myocardial injury [40].…”
Section: Discussionmentioning
confidence: 99%